High vagal tone predicts pulmonary vein reconnection after cryoballoon ablation for paroxysmal atrial fibrillation. Issue 12 (26th November 2021) - Călburean, Paul‐Adrian; Osorio, Thiago Guimaraes; Sorgente, Antonio; Almorad, Alexandre; Pannone, Luigi; Monaco, Cinzia; Miraglia, Vincenzo; Al Housari, Maysam; Mojica, Joerelle; Bala, Gezim; Bisignani, Antonio; Lipartiti, Felicia; et al.
Abstract: Background: Pulmonary vein (PV) isolation is an established treatment for paroxysmal drug‐refractory atrial fibrillation (AF). High parasympathetic tone and reconnection of PVs have demonstrated to be possible culprits of AF recurrence after ablation. Our aim was to investigate the association between parasympathetic tone and reconnected PVs in patients with paroxysmal AF. Methods: Consecutive patients who underwent a redo catheter ablation procedure for atrial tachyarrhythmia recurrence by means of 3D electroanatomic mapping with documentation of presence or absence of PVs reconnection following an initial procedure of cryoballoon (CB) ablation for symptomatic drug‐refractory paroxysmal AF were screened for the study. Results: A total of 92 patients were included, of whom 50 (54.35%) were males. Reconnected PVs were found in 64 (69%) patients. PVs reconnection could be predicted by DC (C‐statistic = .770), by SDNNI (C‐statistic = .714) and by absolute VLF power (C‐statistic = .722), while right‐sided PVs reconnection could be better predicted by DC (C‐statistic = .848) and by SDNNI (C‐statistic = .761). In multivariate binary logistic regression analysis, a DC value ≥6.45 ms and an absolute VLF power value ≥160 ms 2 were associated with three times and five times higher odds of PVs reconnection, respectively. On a vein‐per‐vein analysis, absolute VLF power ≥160 ms 2 was associated with three times higher odds, while reaching of −40°C within 60 s was associated with three times lower odds of PVs reconnection. Conclusion: High parasympathetic tonus accurately predicts PVs reconnection. On a vein‐per‐vein analysis, parasympathetic markers along with biophysical parameters predicted PVs reconnection. On a case‐by‐case analysis, parasympathetic markers were the only predictors of PVs reconnection, thus being a robust PVs reconnection prediction tool.